Wybrane aspekty prawne monitoringu w miejscu pracy - Zajkowska, Marta (Kwartalnik Prawa Publicznego, 2013)
The aim of this article is discussing problems of monitoring of an employee in a workplace in the light of obligatory law. The author mentions different forms of monitoring and he underlines that monitoring of employee is the most frequent form of control used by the employers. At the same time, in present legal state there aren’t any law regulations which directly concern monitoring application in a workplace. The author, through analysis of code of work regulations and the act about protection of personal data, tries to answer the question if these legal regulations are applicable to the problems discussed. And if so, whether they sufficiently protect the employee’s right to privacy in a workplace and whether they assure the protection of personal data of the employee which are processed as a result of monitoring application.